Improving the efficiency of chemical control method weeds in corn for grain under the right bank forest steppe of Ukraine - Мовчан, Ігор Володимирович (Eastern-European Journal of Enterprise Technologies, 2014)
The main task of modern technologies of growing maize for grain is to obtain maximum yields, the solution of which is impossible without effective weed control. Herbicides are among the most effective measures to reduce weed infestation. However, long use of herbicides in maize crops decreases their efficiency. As a result of literature sources analysis, it was found that solving this problem is possible using surfactants and tank mixtures of herbicides in working solutions of herbicides. At the same time, there are no data on the influence of ammonium nitrate, Folicare and Enposan as surfactants on the efficacy of herbicides Milagro and Titus. Using tank mixtures of herbicides Milagro, Calista combined with surfactant ATPlus in maize crops for grain also remains uninvestigated. It is determined that mixed type of weed-infestation, among which late spring types of Echinochloa crus-galli (L.) Roem., Setaria glauca L., Galinsoga parviflora Cav., Chenopodium album L., Amaranthus retroflexus L. take the largest share, is formed in maize crops. The basic amount of weeds appears during the period 30.05-20.06. It is found that a significant decrease in the yield of 0.34 and 0.28 t/ha is observed in the presence of 10 pieces/m2 of plants of Echinochloa cruss-galli L or 15 pieces/m2 of Chenopodium album L respectively. Using surfactants in the working solutions of herbicides improves phytotoxicity and allows to reduce the consumption rate of preparations by 25 %.To expand the action range of preparations and the presence of weeds of different biological groups in maize crops it is necessary to use the tank mixture of herbicides Milagro, 1.0 l/ha, Callisto, 0.25 l/ha and ATPlus 1.0 l/ha. A number of measures, which ensure improving chemical method of weed control and increasing maize yield, is proposed.